2019
DOI: 10.1002/jcla.23052
|View full text |Cite
|
Sign up to set email alerts
|

A‐kinase interacting protein 1 might serve as a novel biomarker for worse prognosis through the interaction of chemokine (C‐X‐C motif) ligand 1/chemokine (C‐X‐C motif) ligand 2 in acute myeloid leukemia

Abstract: Background This study aimed to explore the association of A‐kinase interacting protein 1 (AKIP1) with chemokine (C‐X‐C motif) ligand (CXCL) 1/CXCL2, and further investigate their correlation with clinical features and prognosis in acute myeloid leukemia (AML) patients. Methods Totally 160 de novo AML patients were recruited, and their bone marrow samples were collected before treatment for detecting the expressions of AKIP1, CXCL1, and CXCL2 by the quantitative polymerase chain reaction. Complete remission (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Hao et al. investigated the relationship between CXCL1/CXCL2, clinical characteristics, and prognosis in patients with AML ( 36 ). Expression of CXCL1 and CXCL2 was detected using quantitative-PCR in bone marrow samples from 160 patients with de novo AML.…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al. investigated the relationship between CXCL1/CXCL2, clinical characteristics, and prognosis in patients with AML ( 36 ). Expression of CXCL1 and CXCL2 was detected using quantitative-PCR in bone marrow samples from 160 patients with de novo AML.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that AKIP1 protein and mRNA expressions were upregulated in patients with MM compared to healthy donors, which was consistent with the previous findings that AKIP1 was upregulated in patients with AML compared to healthy controls. 12 The ROC curve analysis further presented good value of AKIP1 in differentiating patients with MM from healthy donors. The possible reasons might include that according to the previous study, activation of NF-κB signaling pathway is associated with several diverse genetic abnormalities, including cytogenetic abnormalities and chromosomal translocation, which lead to the initiation and progression of malignant MM events.…”
Section: Discussionmentioning
confidence: 80%
“… 7 , 8 As a key regulator of NF-κB signaling, AKIP1 is implicated in various aspects of physiological and biological activities (such as immunoinflammatory responses, cell metabolism), which serve as an oncogenic factor in pathogenesis of leukemia and solid cancers. 9 - 13 Functionally, AKIP1 promotes tumor angiogenesis and lymphangiogenesis via activating downstream oncogenes expression of NF-κB signaling in several solid tumors. 11 , 14 , 15 Regarding the role of AKIP1 in hematological malignancies, clinically, AKIP1 is associated with poor risk stratification and worse prognosis in patients with acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting, its tumor expression was positively associated with tumor size, extrathyroidal invasion, pT stage, and pN stage in PTC patients. The probable explanations were as follows: (a) AKIP1 might activate multiple oncogenic signaling pathways (including Wnt/β‐catenin signaling) to promoting the tumorigenicity of PTC; hence, tumor tissue of PTC was characterized by increased AKIP1 expression compared to adjacent tissue 18 . (b) Upregulated ARIP1 (as its role in gastric cancer) could induce Slug‐induced EMT to promote cell proliferation, cell invasion and cell migration to facilitate tumor growth and metastasis, which further accelerated tumor progression and extrathyroidal invasion in PTC patients 15 .…”
Section: Discussionmentioning
confidence: 99%